2017
DOI: 10.1016/j.jag.2017.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the expansion of galamsey gold mines in the cocoa growing area of Ghana using optical remote sensing

Abstract: Artisanal gold mining (galamsey) and cocoa farming are essential sources of income for local populations in Ghana. Unfortunately the former poses serious threats to the environment and human health, and conflicts with cocoa farming and other livelihoods. Timely and spatially referenced information on the extent of galamsey is needed to understand and limit the negative impacts of mining. To address this, we use multi-date UK-DMC2 satellite images to map the extent and expansion of galamsey from 2011 to 2015. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
45
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 25 publications
(34 reference statements)
0
45
1
Order By: Relevance
“…For example, Kervankiran, Dziwornu, and Temurçin (2016) study showed that galamsey activities contribute to the loss of agricultural lands, biodiversity loss, and reduction in rainfall patterns. Similarly, using remote sensing technology, Snapir, Simms, and Waine () estimated that galamsey activities in cocoa‐growing areas in Ghana more than tripled between 2011 and 2015, resulting in the encroachment of about 603 protected forest reserves. These expansions of galamsey activities are also known to pose threats to health due to poor safety procedures (Amankwah & Anim‐Sackey, ; Masterwille, ).…”
Section: Formalizing Ghana's Galamsey Economy: Issues and Prospectsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Kervankiran, Dziwornu, and Temurçin (2016) study showed that galamsey activities contribute to the loss of agricultural lands, biodiversity loss, and reduction in rainfall patterns. Similarly, using remote sensing technology, Snapir, Simms, and Waine () estimated that galamsey activities in cocoa‐growing areas in Ghana more than tripled between 2011 and 2015, resulting in the encroachment of about 603 protected forest reserves. These expansions of galamsey activities are also known to pose threats to health due to poor safety procedures (Amankwah & Anim‐Sackey, ; Masterwille, ).…”
Section: Formalizing Ghana's Galamsey Economy: Issues and Prospectsmentioning
confidence: 99%
“…The idea of formalizing ASM is often a subject of intense debate because formalization varies across countries and contexts and has no clear-cut definition (Singo & Seguin, 2018). However, for this study, formalization means "to speak of individual and group rights: the right to mine, the right to land title, and the right to minerals" (Siegel & Veiga, 2009, p. 52).…”
Section: Formalizing Ghana's Galamsey Economy: Issues and Prospectsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this way, Díez et al, [15] found that mean Hg levels were greater in people living close to industrial mining activity sites compared with a site placed hundreds of kilometers away. To our knowledge, in Africa, the impact of Hg contamination has not been thoroughly studied and the human exposure assessment has been very limited, despite the fact that artisanal and small-scale gold mining continues to expand and to increase in some hotspots in African countries, in response to the global demand for gold [12,[16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Again, Snapir et al extensively mapped and discussed the spatial-temporal dynamics of "galamsey" activities. Their work revealed that the activity has tripled within four (4) years, from 2011 to 2015 and have directly encroached major forest reserves [17]. However, to be informed about the size and extent of degradation is inadequate when it comes to representing these degradation situation for policy implication purposes, yet, little has been ushered into quantifying the ecosystem services such as the food production, air purification, carbon storage, etc., that are lost due to these technological loads.…”
Section: Introductionmentioning
confidence: 99%